Needs Analysis for Designing English for Tourism Practitioners at Bayan Village Using A Standpoint Model - Mutmainah, Holizatul; Sujana, I Made; Saputra, Agus; Fitriana, Eka (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aimed to improve vocabulary and grammar skills for tourism practitioners in Bayan Village and to design teaching English for tourism practitioners using Standpoint Model. A qualitative descriptive research design was employed to explore the specific English language needs of ten tourism practitioners, including chief of tour guides, tour guides, the weavers of Poleng and Londong Abang, souvenir sellers, and Bayan village specialty drink. The research was conducted in Bayan Village, North Lombok. Data collection procedures included observation, interview, and documentation, while the instruments used comprised observation sheets and interview sheets. The results of this research showed that the syllabus was created for tourism practitioners in Bayan Village, the English language learning design was designed using the Standpoint Model, which focuses on the specific needs of tourism practitioners based on their context and work environment by determining authentic tasks and texts used to develop a syllabus designed to meet their needs, this model involves: Needs Analysis, Determining Authentic Tasks and Texts, Designing Learning Objectives, Selecting Content and Methods, and Assessment. English learning can be more relevant and effective in improving the communication skills of tourism practitioners, thus supporting the development of sustainable tourism in Bayan Village.